2016
DOI: 10.2105/ajph.2016.303326
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Consequences of Obesity

Abstract: The NHS cohorts have contributed to our understanding of the risk factors for and consequences of obesity and made a lasting impact on clinical and public health guidelines on obesity prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
432
0
29

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 582 publications
(475 citation statements)
references
References 45 publications
14
432
0
29
Order By: Relevance
“…Overweight and obesity is a major health issue in Australia, with 35.4% of Australians aged 18 years and above being overweight and 27.5% being obese . This has mainly been attributed to excess energy intake, and low physical activity levels . In 2008, it was estimated that the overall cost of obesity to Australian society was $58.2 billion .…”
Section: Introductionmentioning
confidence: 99%
“…Overweight and obesity is a major health issue in Australia, with 35.4% of Australians aged 18 years and above being overweight and 27.5% being obese . This has mainly been attributed to excess energy intake, and low physical activity levels . In 2008, it was estimated that the overall cost of obesity to Australian society was $58.2 billion .…”
Section: Introductionmentioning
confidence: 99%
“…Lopez (2014) identified that urban sprawl and location of an individual's residence was associated with obesity and should be account for. Further, dietary, lifestyle, and genetic composition, as well as gene-environment interactions were all unaccounted for in this research but have been shown to be determinants of obesity (Hruby et al, 2016). Further, the models only offer a small sample size and may suffer bias due to this.…”
Section: Resultsmentioning
confidence: 86%
“…Two key reasons for increasing the prevalence of overweight and obesity are increased energy intake and decreased energy expenditure. Increased energy consumption has been through the increased availability and consumption of energy dense foods [10], while decreased energy expenditure has occurred through decreasing physical activity as a result of easier accessibility to motorized transport, low request for physical activity for subsistence and household management; and well developed sedentary habits [32,33]. To prevent overweight and obesity a number of activities are suggested.…”
Section: Discussionmentioning
confidence: 99%